2017
DOI: 10.3389/fmars.2017.00213
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Transcriptional Levels of RuBisCO Form II of Sulfur-Oxidizing γ-Proteobacteria in Coastal-Upwelling Waters with Seasonal Anoxia

Abstract: Seasonal wind-driven upwelling, high primary production in surface waters, and oxygen deficiency in subsurface waters characterize the coastal ecosystem of the subtropical eastern South Pacific (ESP), and shape the nature and dynamics of the microbial community structure and function. We investigated the diversity, abundance, and transcriptional levels of the gene encoding the large subunit form II of the RuBisCO enzyme (cbbM) in the pelagic microbial community at a continental-shelf site off central Chile ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Sulfur plumes can also be transported into the offshore OMZ (> 200 m water depth) due to lateral transport processes (e.g., mesoscale eddies). (A,B) Remote sensing images of sulfur plumes using the water-leaving reflectance wavelength of 560 nm (optimal waveband for sulfur plume detection; Ohde et al 2007;Ohde and Dadou 2018) Léniz et al 2017. Shown are the maximum ccbM copy numbers of the three sampled depths by Léniz et al 2017.…”
Section: Sulfidic Events and Sulfur Cycling Associated With The Upper Shelfmentioning
confidence: 99%
“…Sulfur plumes can also be transported into the offshore OMZ (> 200 m water depth) due to lateral transport processes (e.g., mesoscale eddies). (A,B) Remote sensing images of sulfur plumes using the water-leaving reflectance wavelength of 560 nm (optimal waveband for sulfur plume detection; Ohde et al 2007;Ohde and Dadou 2018) Léniz et al 2017. Shown are the maximum ccbM copy numbers of the three sampled depths by Léniz et al 2017.…”
Section: Sulfidic Events and Sulfur Cycling Associated With The Upper Shelfmentioning
confidence: 99%
“…In fact, closely related sequences to Ca . Nitromaritima were numerically dominant in OMZ metagenomes in the ETSP off northern Chile as well as in metatranscriptomes in the subtropical ESP off Concepción (Léniz et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Two mechanisms could explain a potentially fish-stimulated response in the number of Nitrospina transcripts. The ammonia excretion from fish can favor the first reaction of nitrification (Eikebrokk & Piedrahita, 1997 (Léniz et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the CBB cycle of photosynthesizers contributes most to the global synthesis of organic matter (Hügler and Sievert, ). Nevertheless, many microorganisms, including the anammox (anaerobic ammonium oxidation) bacteria (Woebken et al ., ) and the abundant sulfur oxidisers (Walsh et al ., ; Schunck et al ., ; Léniz et al ., ) in AMZs, have the genetic potential for carrying out autotrophic carbon fixation in dark marine ecosystems (Swan et al ., ). Previous studies that have measured carbon fixation rates in the ETSP AMZ have reported a peak of values ranging from 9 to 130 nmol C L −1 d −1 below the photic zone (100–500 m), which has been attributed to the dark autotrophic carbon fixation (Löscher et al ., ; Callbeck et al ., ).…”
Section: Introductionmentioning
confidence: 99%